Effects of Feed Type, Sex and Plumage Condition on Tonic Immobility and Blood Parameters in Broilers - Akpa, G.N.; Koffi, K.A.; Hassan, M.R.; Kabir, M.; Duru, S.; Yashim, S.M. (International Journal of Poultry Science, 2007)
The aim of this study was to determine the effects of feed type, sex and plumage condition on tonic immobility and blood parameters in broiler birds. Eighty broiler birds of Anak (2000) breed were raised from day-old to 8 weeks of age. They were randomly divided into 4 groups of 20 birds each. A different type of feed was given to each group from day-old to 8 weeks of age. The birds were raised on deep litter in the first 4 weeks, and later they were raised in battery cages for the remaining 4 weeks. Tonic immobility of the birds was determined between 0 and 600 seconds. Blood parameters were also determined. Results obtained indicated that generally, tonic immobility was averagely good (less than 300 seconds) with birds fed with feed type 4 having the best (shortest) tonic immobility. Also, tonic immobility was influenced by plumage condition. The normal ranges of Packed Cell Volume (PCV), Haemoglobin (Hb) concentration and total plasma protein were used to arrive at the fact that feed type and plumage condition influenced tonic immobility and blood parameters. Males had better (shorter) tonic immobility than females.